2020
DOI: 10.1039/d0cb00033g
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biophysical insights into the mode of covalent binding of rationally designed potent BMX inhibitors

Abstract: We identified potent, functionalisable BMX inhibitors and revealed their covalent mode of binding to BMX by X-ray crystallography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…The rate of inactivation ( k inact / K I ) is a second-order event, which describes the efficacy of the covalent bond binding event. To characterize the covalent interactions of JS25 with BTK, evaluation of the irreversible binding efficacy was performed as previously described . Additionally, we included ibrutinib, acalabrutinib, and BMX-IN-1 (Figure a).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The rate of inactivation ( k inact / K I ) is a second-order event, which describes the efficacy of the covalent bond binding event. To characterize the covalent interactions of JS25 with BTK, evaluation of the irreversible binding efficacy was performed as previously described . Additionally, we included ibrutinib, acalabrutinib, and BMX-IN-1 (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we had previously shown that JS25 did not react with other Scr kinases. 23 On comparing the JS25 selectivity profile with other BTKi (Supporting Table S3), we find that JS25 is less reactive than ibrutinib for TEC, TXK, ITK, EGFR, JAK3, BLK, and Her2; less reactive for TEC and TXK than acalabrutinib; less reactive toward EGFR, JAK3, and Her2 than zanubrutinib; and less reactive toward TEC, TXK, and BLK than tirabrutinib, although slightly more reactive against ITK. The BTKi acalabrutinib, zanubrutinib, and tirabrutinib are secondgeneration inhibitors, and relative to ibrutinib, these molecules presented fewer "off-target" effects in early clinical trials.…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, recently there have been successful examples of PROTACs using covalent warheads that have degraded a range of targets, including ERK1/2 (Lebraud et al, 2016), Bruton tyrosine kinase (BTK) (Xue et al, 2020), and KRAS G12C (Bond et al, 2020). There have also been examples of TCIs that degrade a target POI themselves, such as the BMX inhibitors BMX-IN-1 and highly potent JS25 (Seixas et al, 2020), but this is beyond the scope of this review.…”
Section: Protacs With Covalent Ligands For the Targetmentioning
confidence: 99%